2001
DOI: 10.1002/1097-0290(20010305)72:5<530::aid-bit1017>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of enzymes on PTFE surfaces

Abstract: Membranes and powders prepared from PTFE (polytetrafluorethylene) were investigated for their potential use as multifunctional supports for enzymes. The obtained bioactive materials are valuable for the construction of biosensors and enzyme reactors. To allow covalent coupling of enzymes to PTFE, the surface of the material was treated with elementary sodium followed by oxidation with ozone or hydrogen peroxide.%Derivatization steps were optimized in order to achieve highest enzyme loading and short reaction t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Miyagawa et al prepared glycosylated cellulose membranes by immobilizing the glycoconjugate polymer on carboxymethylated membranes through condensation reaction between the amino group of the glycoconjugates and the carboxyl group of the cellulose. Keusgen and coworkers pretreated polytetrafluoroethylene (PTFE) membrane with elementary sodium followed by oxidation using ozone or hydrogen peroxide, and then mannose ligands were immobilized on the membrane surface through coupling reagent, 1,4‐butanediol diglycidyl ether. Tabary et al modified PVDF membranes by impregnating them with the reactants of saccharide derivate (cycldextrin, maltodextrin, and citric acid) in a thermofixation oven.…”
Section: Glycosylation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Miyagawa et al prepared glycosylated cellulose membranes by immobilizing the glycoconjugate polymer on carboxymethylated membranes through condensation reaction between the amino group of the glycoconjugates and the carboxyl group of the cellulose. Keusgen and coworkers pretreated polytetrafluoroethylene (PTFE) membrane with elementary sodium followed by oxidation using ozone or hydrogen peroxide, and then mannose ligands were immobilized on the membrane surface through coupling reagent, 1,4‐butanediol diglycidyl ether. Tabary et al modified PVDF membranes by impregnating them with the reactants of saccharide derivate (cycldextrin, maltodextrin, and citric acid) in a thermofixation oven.…”
Section: Glycosylation Methodsmentioning
confidence: 99%
“…It has been reported that β(1 → 4) galactosyltransferase expressed as a fusion protein with binding MBP‐galactosyltransferase was displayed specifically on a Langmuir–Blodgett membrane through maltotriose‐MBP interaction . Alliinase was also immobilized on PTFE membrane surface indirectly by a saccharide‐lectin binding . The saccharide mannan was bound to the membrane surface as an anchor for layers of Con A.…”
Section: Applications Of the Glycosylated Membranesmentioning
confidence: 99%
“…As we showed in a previous study, APTES-coated glass substrates are functional up to 3 months of storage at room temperature or 4 °C, after which hydrolysis significantly reduces the receptor immobilization efficiency. Similarly, thiols such as 11-mercaptoundecanoic acid (MUA) have been used to generate COOH functional groups on gold-based substrates. On the other hand, acid/base treatments and highly reactive ionized gas plasmas have been used to generate NH 2 or COOH functional groups on thermoplastic substrates such as poly­(methyl methacrylate) (PMMA), , polytetrafluoroethylene (PTFE), , and polycarbonate (PC) . Using covalent immobilization strategies, typical desirable b max values ranging from 10 –9 to 10 –7 mol/m 2 can be obtained, , whose values mimic the distribution of receptors on surfaces of cells …”
Section: Enhancing Analytical Sensitivity and Specificitymentioning
confidence: 99%